The effects of ratings-contingent regulation on international bank lending behavior: Evidence from the Basel 2 Accord - Hasan, Iftekhar; Kim, Suk-Joong; Wu, Eliza (Journal of Banking & Finance, 2015)
We investigate the effects of credit ratings-contingent financial regulation on foreign bank lending behavior. We examine the sensitivity of international bank flows to debtor countries’ sovereign credit rating changes before and after the implementation of the Basel 2 risk-based capital regulatory rules. We study the quarterly bilateral flows from G-10 creditor banking systems to 77 recipient countries over the period Q4:1999 to Q2:2013. We find direct evidence that sovereign credit re-ratings that lead to changes in risk-weights for capital adequacy requirements have become more significant since the implementation of Basel 2 rules for assessing banks’ credit risk under the standardized approach. This evidence is consistent with global banks acting via their international lending decisions to minimize required capital charges associated with the use of ratings-contingent regulation. We find no evidence to suggest that banking regulation induced foreign lending has heightened the perceived sovereign credit risks of recipient countries.